Fatal Cases of 2009 Pandemic Influenza A (H1N1) in Korea - Kim, Hyun Su (The Korean Academy of Medical Sciences, 2011)
The aim of this study was to describe the features of deaths associated with the 2009 pandemic influenza A (H1N1) by 26 November 2009 in Korea. We collected standardized case reports on 115 confirmed deaths through a nationwide enhanced influenza surveillance system. The median age was 61 yr (interquartile range [IQR], 0.2-97 yr) and 58 (50.4%) were females. The case fatality rate was estimated as 16 per 100,000 cases. The age-related mortality rate had a J-shaped curve. Eighty-three patients (72.2%) had at least 1 underlying medical disease. Bacterial co-infections were detected in the blood or sputum specimens from 34 patients. Of the 63 patients who were hospitalized in the intensive care unit (ICU), the median time from symptom onset to hospital admission was 2 days (IQR, 0-22 days), and the median time from hospitalization to ICU admission was 1 day (IQR, 0-17 days). Neuraminidase inhibitors were administered to 100 patients (87.0%), 36% of whom began treatment within 2 days. In conclusion, fatal cases from the 2009 influenza A (H1N1) infection in Korea are mainly aged individuals with underlying disease, and associated with pneumonia, bacterial co-infections, and multi-organ failure.